PEMBERDAYAAN KADER PERTOLONGAN PERTAMA TENTANG LIFTING MOVING DAN SYNCOPE PADA MASYARAKAT RAWAN TERJADI KECELAKAAN LALU LINTAS : Pengabdian Masyarakat di RT 005 RW 001 Dusun Kepung Tengah Kabupaten Kediri - MOCH. MAFTUCHUL HUDA; Andika Siswoaribowo; Indasah (STIKES dan AKZI Karya Husada Kediri, 2022)
Traffic accidents are a frequent and unfortunate event that can take lives, these accidents occur due to several factors, such as human error, vehicles that do not meet standards, poor roads, and environmental factors such as weather. bad. First aid in traffic accidents can be an opportunity for people who live on the edge of the highway. The purpose of community service is to empower community cadres who have been formed to make the community capable/empowered in carrying out first aid regarding lifting moving and syncope in RT 005 RW 001 Dusun Kepung Tengah. The implementation method is carried out by forming traffic accident first aid cadres to be trained by using lecture and demonstration methods about lifting moving and syncope first aid until they become competent (competent) in empowering first aid cadres about lifting moving and syncope. Furthermore, the cadres who have been empowered will convey how to carry out first aid lifting moving, and syncope with lecture and demonstration methods so that the community becomes able to carry out first aid about lifting moving, and syncope independently without having to wait for the health team to arrive. The results of the ability of first aid carried out by cadres changed from good category (67%) to very good (100%), while for the majority of people who had sufficient ability (55%) to good (44%). The conclusion is that all cadres and the community who have been empowered can carry out first aid lifting moving and syncope well. Suggestions are that lifting moving and syncope first aid training can be continued until all people who live on the edge of the highway are prone to traffic accidents and receive training and can independently carry out lifting moving and syncope first aid.